A (in)efetividade do combate ao trabalho infantil em megaeventos: as ações do Ministério Público do Trabalho da 2ª região - Patrocínio Júnior, Carlos Alberto do (2022)
This work reflects on the questioning about the (in)effectiveness of combating child labor in mega-events, having as reference the actions of the Public Ministry of Labor of the 2nd Region (MPT2) in promoting procedures to combat child labor during the World Cup FIFA 2014, the carnival and the matches of the Brazilian Football Championship held in São Paulo in 2015, with a view to protecting children and teenagers, through its action group to combat child labor. With this, the study was developed to analyze the trajectory of legislation regarding Brazilian children and adolescents and the fight against child labor. From this perspective, the trajectory of slavery and its remnants on the issue of child labor was first analyzed. Likewise, there was an exposition on the trajectories of the doctrines: from the irregular situation to full protection and the Ministry of Labor (MT) in the fight against child labor for its eradication. In addition, special attention was given to the role of the National Forum for the Prevention and Eradication of Work (FNPETI). Then, it was observed how the historical evolution of the Public Ministry (MP) and the emergence of the Public Ministry of Labor (MPT) in Brazil took place. Soon after, the research was dedicated to analyzing the role of the MPT in combating and eradicating child labor. Next, an outline was made about the performance of the MPT2, pointing to its most relevant principles to this study and its purpose. Then, the PROMOs requested from the MPT2 were presented, which were related to the actions developed during the 2014 World Cup mega-events, the Brazilian Championship and the 2015 Carnival. , based on textual genre, relevance to the topic addressed and typology of actions, now referred to as action of social persuasion, repressive action and ostensive-preventive action. From that point onwards, the documents were analyzed under the criteria of a qualitative research methodology, as it is an approach that makes it possible to explain the actions and observe their consequences and repercussions. This examination was carried out in the light of the systematization carried out from the identification of the impacts that such actions generated on society, as proposed in the general objective of this work. Finally, it is concluded, through the analysis of the collected documents and reflection, and from the social point of view, that there was the effectiveness of actions related to combating child labor in the main mega-events of 2014 and 2015